DOES THE COMMUNITY'S PERSPECTIVE ENCOURAGE CUSTOMERS TO TAKE FINANCING PRODUCTS AT SHARIA BANK? - Syahriyatul Muharromah; Nurul Huda; Muslikh Muslikh; Nova Rini (Universitas Airlangga, 2023)
This study aims to determine community interest in financing products at Islamic banks with a modified Theory Planned Behavior (TPB) approach. These modified TPB variables consist of knowledge, religiosity, attitudes, subjective norms and behavioural control. This research was conducted in Jakarta. Islamic banks located in the Jakarta area are the object of this research, and the sample is 130 respondents. The quantitative method with the Partial Least Square (PLS) analysis model approach with SmartPLS 2.0 software is the method used in this study. The variables of knowledge, religiosity, attitudes, subjective norms and behavioural control are exogenous, while the intervening variable is community interest, and the endogenous variable is financing decisions. The variables of knowledge, religiosity, attitudes, subjective norms and behavioral control, which have a direct positive and significant effect on the community's interest in using Islamic bank financing products, are the results of this study. Knowledge, Attitude and behavioural control directly and significantly positive affect the community's decisions to choose financing products in Islamic banks. The higher people's knowledge, Attitude and behavioural control, the higher the financing decision becomes the implications of this research result. Religiosity and subjective norms significantly negatively affect the decision to choose financing products in Islamic banks. In addition, community interest also has a positive and significant effect on financing decisions. This means that, community interest can significantly mediate knowledge, religiosity, subjective norms, attitudes, and behavioral control influence financing decisions. Based on the research results, Indonesian Islamic Banks can develop business by emphasizing the religiosity side to inspire people to prefer financing of Islamic banks over conventional banks. Furthermore, Bank Syariah Indonesia should use social-environmental reference factors like friends, family, neighbors and religious figures